ANALYSIS OF ACCOUNTING INFORMATION SYSTEM RECEIVING AND SPENDING OF BOS IN THE COVID-19 ERA - Nadia Maya Sari (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2022)
The purpose of this research were to described the management of BOS fund at MTs Islamiyah Palangka Raya in the era of the covid-19 pandemic, and analyzed the accounting information system for inflowing and expenditure BOS fund, was it according to BOS technical instructions or not. The object of this research was MTs Islamiyah Palangka Raya. The calibration was carried out by looking at the facts regarding the accounting information system for inflowing and expenditure of fund BOS in the era of the covid-19 pandemic. This research used ethnography with descriptive method. The data collection used were documentation and interview with headmaster, exchequer, and students of this school. The results of this resarch showed, that the management of BOS funds at MTS Islamiyah in the era of the covid-19 pandemic based on the Decree of the Director General of Islamic Education No. 6572 of 2020 about Technical Guidelines of BOP and RA at madrasas for the fiscal year 2021 based on 5 principles, still not optimal yet because there was 1 principle that has not been fulfilled, namely the principle of efficiency. Afterward, the accounting information system for cash receipts and expenditure of BOS funds is quite good, although there was one indicator that has not been fulfilled, which there was not a document flow chart at MTs Islamiyah which will be a suggestion from the researcher for MTS Islamiyah Palangka Raya. When did the resarch, it was found that there was a gap between the amount of BOS funds received and the school's needs, due to the system of determining the budget based on the number of students.. Keywords: Accounting Information System, cash receipts and disbursements, Covid-19